2022
DOI: 10.3389/fped.2021.790839
|View full text |Cite
|
Sign up to set email alerts
|

Low Vitamin D Levels at Birth and Early Respiratory Outcome in Infants With Gestational Age Less Than 29 Weeks

Abstract: BackgroundVitamin D (VitD) is involved in lung development but its influence on respiratory distress syndrome of extremely preterm (EPT) infants have been little investigated. In this study, we examined the influence of low vitamin D status at birth on early respiratory outcomes of this vulnerable infant population.MethodsCord blood 25(OH)D levels ≤ 75 nmol/L were considered as Low vitamin D levels. Stepwise logistic regression and classification regression-tree analyses were used and the primary outcome was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…We chose to study 25(OH)D at the first month because the frequency of excessive concentrations at birth in preterm infants is very low [31][32][33]. In France, Courbebaisse et al reported that in the general population of newborns, 93% of cord blood concentrations were below 75 nmol/L [34], and Papalia et al reported that in infants born below 29 weeks gestational age, 74% had a cord blood concentration ≤75 nmol/L [35]. In France, the current recommendation for vitamin D supplementation during pregnancy is to administer 100,000 IU once during the seventh month of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to study 25(OH)D at the first month because the frequency of excessive concentrations at birth in preterm infants is very low [31][32][33]. In France, Courbebaisse et al reported that in the general population of newborns, 93% of cord blood concentrations were below 75 nmol/L [34], and Papalia et al reported that in infants born below 29 weeks gestational age, 74% had a cord blood concentration ≤75 nmol/L [35]. In France, the current recommendation for vitamin D supplementation during pregnancy is to administer 100,000 IU once during the seventh month of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, vitamin D deficiency contributes to several respiratory complications and lung function impairments in premature infants, including airway hyperresponsiveness, increased resistance, and reduced compliance ( 15 , 40 ). However, the association between vitamin D status and the development of BPD remains controversial in clinical research due to the multifactorial etiology of BPD ( 8 , 9 , 12 , 41 ). Moreover, vitamin D deficiency is not the sole risk factor for BPD, and the risk factors and infants included in analysis vary across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models of maternal gestational vitamin D deficiency have been reported to impair the bronchiolo–alveolar structure, reduce alveolar density and lung volume in the fetus, and affect long-term pulmonary dysfunctions [ 8 , 10 ]. Observational studies have shown a relationship between maternal gestational vitamin D deficiency and respiratory diseases in preterm and term infants, including respiratory distress syndrome, wheezing events, asthma, and hospital admissions for respiratory tract infections during infancy [ 11 , 12 , 13 , 14 , 15 , 16 ]. However, randomized studies have reported inconsistent effects relating to the maternal gestational Vitamin D3 supplementation of the offspring’s respiratory outcomes [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%